Strategic Energy Partnership between Russia and China - Baboshkin, Pavel (International Journal of Energy Economics and Policy, 2020)
During recent years the role of energetic security in Russia steadily increases. After deterioration Russian relations with West countries in energy sector stay single stable economic tool, which Russia use for the maintenance of impact in surrounding region. Instability of the importers market which is priority for the country, bounded with excitements about use by Russia theirs position on the energetic, markets for reaching political goal through the development of projects such as Nord Stream 2 and Turkish stream. In its turn in latest decade, Russia aspires to ensure solid positions in Siberia and Far East. American companies refuse to participate in the execution of orders for Russia due to the unstable political situation and stricter restrictive and regulatory measures, which makes the level of risk of cooperation unacceptable. Using alternative sources of electricity, Russia and China can extract many positive effects: financial income, employment, energy security for the domestic market, etc. For example, in the Far East, the import of fuel can be reduced by 40% after the implementation of RAO UES plans to build 178 renewable energy sources with a total capacity of 146 mW. Keywords: strategic partnership, economic development, energy cooperation, Asian-Pacific region, energy security JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.9032